2013
DOI: 10.4048/jbc.2013.16.4.442
|View full text |Cite
|
Sign up to set email alerts
|

Random Synchronous Malignancy in Male Breast: A Case Report

Abstract: We report here a case of a random synchronous male breast malignancy in a patient with a known base of tongue malignancy that was incidentally detected on a whole body 18-fluorine deoxyglucose positron emission tomography and computed tomography (18F-FDG PET/CT). Patient was referred to us for PET/CT staging and radiotherapy planning for a poorly differentiated squamous cell carcinoma of base of tongue. Histopathologically, the incidentally detected breast lesion was proven to be an invasive ductal carcinoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…31 The relative lack of glandular activity in the male breast potentially increases the sensitivity of FDG PET/CT for detection of male breast cancer. 70 , 71 Groheux et al have reported that FDG PET/CT seems to be a powerful imaging method to perform staging, restaging, and treatment response assessment in male patients with breast carcinoma. They found that all the estrogen receptor positive breast carcinomas were FDG-avid (Fig.…”
Section: Diseases Of the Male Breastmentioning
confidence: 99%
“…31 The relative lack of glandular activity in the male breast potentially increases the sensitivity of FDG PET/CT for detection of male breast cancer. 70 , 71 Groheux et al have reported that FDG PET/CT seems to be a powerful imaging method to perform staging, restaging, and treatment response assessment in male patients with breast carcinoma. They found that all the estrogen receptor positive breast carcinomas were FDG-avid (Fig.…”
Section: Diseases Of the Male Breastmentioning
confidence: 99%
“…The two tumors must be sufficiently distant from each other, 3) It should be excluded with certainty that the second tumor is not the metastasis of the index tumor (6). Synchronous tumors in our case fulfilled all three criteria.…”
Section: Discussionmentioning
confidence: 78%
“…Multiple primary carcinoma descriptions are provided with the following criteria: each malignant tumor must bear histological features; they must be different from each other histologically; exclusion must be done as they are not metastasis of each other [3].…”
Section: Discussionmentioning
confidence: 99%